Do cash transfers improve birth outcomes? Evidence from matched vital statistics, social security and program data - Veronica Amarante; Marco Manacorda; Edward Miguel; Andrea Vigorito (Institute for the Study of Labor (IZA), 2011)
There is limited empirical evidence on whether unrestricted cash social assistance to poor pregnant women improves children's birth outcomes. Using program administrative micro-data matched to longitudinal vital statistics on the universe of births in Uruguay, we estimate that participation in a generous cash transfer program led to a sizeable 15% reduction in the incidence of low birthweight. Improvements in mother nutrition and a fall in labor supply, out-of-wedlock births and mother's smoking all appear to contribute to the effect. We conclude that, by improving child health, unrestricted unconditional cash transfers may help break the cycle of intergenerational poverty.
urn:nbn:de:101:1-201202285003
Keywords: J88; I38; J13; 330; welfare transfers; birth outcomes; Bevölkerungspolitik; Frauen; Schwangerschaft; Sozialtransfer; Kinder; Gesundheit; Bevölkerungsentwicklung; Uganda